In Vivo Biocatalytic Cascades Featuring an Artificial‐Enzyme‐Catalysed New‐to‐Nature Reaction. (30th November 2022) - Ofori Atta, Linda; Zhou, Zhi; Roelfes, Gerard
Abstract: Artificial enzymes utilizing the genetically encoded non‐proteinogenic amino acid p‐ aminophenylalanine (pAF) as a catalytic residue are able to react with carbonyl compounds through an iminium ion mechanism to promote reactions that have no equivalent in nature. Herein, we report an in vivo biocatalytic cascade that is augmented with such an artificial enzyme‐catalysed new‐to‐nature reaction. The artificial enzyme in this study is a pAF‐containing evolved variant of the lactococcal multidrug‐resistance regulator, designated LmrR_V15pAF_RMH, which efficiently converts benzaldehyde derivatives produced in vivo into the corresponding hydrazone products inside E. coli cells. These in vivo biocatalytic cascades comprising an artificial‐enzyme‐catalysed reaction are an important step towards achieving a hybrid metabolism. Abstract : We report in vivo biocatalytic cascade reactions comprising a combination of canonical enzyme‐catalysed reactions with an artificial‐enzyme‐catalysed new‐to‐nature reaction. The artificial enzyme contains a genetically encoded unnatural catalytic residue, which catalyses the formation of a hydrazone product from biosynthetically produced benzaldehydes in E. coli .